2005
DOI: 10.1029/2005jb003692
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to special section: Stress transfer, earthquake triggering, and time‐dependent seismic hazard

Abstract: [1] In this introduction, we review much of the recent work related to stress transfer, earthquake triggering, and time-dependent seismic hazard in order to provide context for the special section on these subjects. Considerable advances have been made in the past decade, and we focus on our understanding of stress transfer at various temporal and spatial scales, review recent studies of the role of fluids in earthquake triggering, describe evidence for the connection between volcanism and earthquake triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
179
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(182 citation statements)
references
References 178 publications
(230 reference statements)
1
179
0
2
Order By: Relevance
“…where Ds is the shear stress change (positive in the fault slip direction), Dr n is the normal stress change (positive for extension), l is the friction coefficient and DP indicates the pore pressure changes, representing the undrained response of the medium on a sufficiently short timescale so that fluid flow cannot occur; at longer timescales the drained response of the medium will modify the pore pressure evolution promoting fluid flow (Steacy et al 2005). A possible undrained pore pressure model is the constant apparent friction model, in which pore pressure is proportional to normal stress changes and Eq.…”
Section: Stress Transfer Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where Ds is the shear stress change (positive in the fault slip direction), Dr n is the normal stress change (positive for extension), l is the friction coefficient and DP indicates the pore pressure changes, representing the undrained response of the medium on a sufficiently short timescale so that fluid flow cannot occur; at longer timescales the drained response of the medium will modify the pore pressure evolution promoting fluid flow (Steacy et al 2005). A possible undrained pore pressure model is the constant apparent friction model, in which pore pressure is proportional to normal stress changes and Eq.…”
Section: Stress Transfer Analysismentioning
confidence: 99%
“…where the apparent friction coefficient l 0 is intended to include the effects of pore fluids as well as the material properties of the fault zone (Harris 1998;Cocco and Rice 2002;Steacy et al 2005). Positive or negative variations of the CFF indicate that the stress field is acting to promote or oppose the rupture, respectively.…”
Section: Stress Transfer Analysismentioning
confidence: 99%
“…where τ and σ n represent the changes in the shear and the normal stresses over the target fault plane, respectively, while µ is the apparent coefficient of the friction (Harris, 1998;Steacy et al, 2005a), which includes the unknown effect of pore fluid pressure and has been postulated to vary in the range 0.2-0.8 (Stein, 1999). The selection of value of µ has been pointed out to be not crucial in affecting the pattern of change in Coulomb failure stress (King et al, 1994;Steacy et al, 2004).…”
Section: Coulomb Stress Changes Analysismentioning
confidence: 99%
“…King et al, 1994;Stein et al, 1997;Harris, 1998;Stein, 1999;Steacy et al, 2004, Steacy et al, 2005a. Because static stress changes caused by an earlier earthquake can promote or delay subsequent earthquakes along nearby faults, earthquake stress changes can be utilised in the interpretation of future seismic hazards or earthquake probabilities (Stein et al, 1997;Nalbant et al, 2002;Utkucu et al, 2003;Parsons, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Fault interaction is predicted on theoretical grounds (e.g. Steacy et al, 2005) and is found to be relevant to the long-term behaviour of fault systems (Marzocchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%